Background Factors of Thai Students’ Speaking Achievement in English Learning - Nurulhuda Marudin; Dwijani Ratnadewi; Waode Hamsia (Tell : Teaching of English Language and Literature Journal, 2018)
In learning English as Foreign Language, there are many background factors that play important roles to be success in learning. In the case of foreign students who study English in non-English speaking country, these factors become more complex. This study aims to analyze the background factors of Thai students’ speaking achievement and the different background factors between student’s high and low scores of speaking achievement. This study used mixed method design as method of study. The theories of factors were used to answer the objective of this research such as self-esteem, inhibition, risk-taking, anxiety, empathy, extroversion, introversion, motivation, attitude, language exposure, and social situation. The subject was five students from Thailand who studied at Muhammadiyah University of Surabaya. The finding was that each of students mostly possessed different background factors. However, their intensity and ability were different among of them. All of those factors were greatly influence their acquiring of TEFL as well. There were two students who had the highest and lowest scores in their speaking achievement after several years they have learned English in Indonesia. The different background factors between both of them were self-esteem, inhibition, risk-taking, anxiety, extroversion, introversion, attitude, and social situation factors. Their background factors in speaking were supported by many factors to reach a good achievement. Therefore, the factors mainly play important roles to tend students learning foreign language successfully.